Death onto Life—A Guide to Edward Albee - Prohászka-Rád, Boróka (Hungarian Journal of English and American Studies, 2020)
Book review: Roudané, Matthew. Edward Albee: A Critical Introduction. Cambridge: Cambridge UP, 2017. 200 pages. ISBN 978-0-521-72695-5. Pbk. £14.99.